COMPARATIVE ANALYSIS OF COMPLEX MECHANICAL PROPERTIES OBTAINED IN TESTS ON FINISHED BOLTS AND TURNED SAMPLES - Gul, Y. P.; Ivchenko, A. V.; Kondratenko, P. V.; Perchun, G. I. (Science and Transport Progress, 2015)
Purpose. The purpose of the work is provided by the system experimental study of the effect of strengthening the level of the ratio of complex mechanical properties of the finished bolts and peeled samples and analysis of the data on the basis of geometric and structural reinforcement. Methodology. A uniaxial tensile test was carried out on full-size bolts and the peeled samples to diameters of 10 mm and 8 mm at a testing machine FP - 100/1 recording full diagram of deformation and fracture. Findings. The level of strength of qualitatively and quantitatively has different effects on the characteristics of the ratio of resistance to plastic deformation and ductility characteristics ductile fracture resistance, determined on the finished bolts and peeled samples. At the same time, the analysis suggests that the combination of mechanical properties determined on finished bolts, the most adequate to their mechanical behavior during operation. This conclusion is particularly important for acceptance testing of bolts of strength class 8.8 or higher. Originality. For the first time experimentally shown that the system is functional cuts on specific metal products can have both hardening and softening effect on the characteristics of resistance to plastic deformation in terms of normal stress depending on the level of hardening and given an interpretation of the observed phenomena on the basis of changes in the ratio of the concentration of eg-tions and the degree of rigidity of the stress state in the cuts. Practical value. Limitation of mechanical tests are only willing bolts, other than greater consistency determines the properties of their structural strength bolts in the operation, reduce the overall time-consuming tests.